RESTRUKTURISASI ORGANISASI DAKWAH YANG KOMPREHENSIP [KAJIAN TERHADAP UPAYA PENJABARAN DAKWAH BERDASARKAN PMANO. 13 TAHUN 2012] - Kholili Kholili (Universitas Islam Negeri (UIN) Mataram, 2017)
Islamic Information Directorate in charge of da’wah Islam, the structure and the task would be a lot of contact with the activities of information da’wah and extension da’wah. But officials in the field of da’wah is unclear, as the structure and tasks should be done. The research problem: How to design the da’wah of Islam in the PMA 13- 2012. How policy makers formulate information da’wah and extension da’wah at all levels of the ministry of religion. Objective: Assess the design of the da’wah of Islam in the PMA 13 - 2012 and analyze how the policy makers to formulate information da’wah and extension da’wah. Research Methods. The study uses a case study to examine many documents that seeks to provide a detailed overview of the PMA 13 - 2012, but some things carefully studied and confirmed to officials associated with FGDs and in-depth interviews. There are many programs, righ now are revolve around administration technical issues, not much goes to the development of da’wah materials and methods strategically. Da’wah program, righ now, there is a program is to overcome problems that appear in society, not to get in to the undertakings of the design strategy for long-term da’wah.